In silico biomechanical analysis of poller screw-assisted small-diameter intramedullary nail in the treatment of distal tibial fractures - Tan, Jinchuan; Yang, Yang; Wang, Mian; Huang, Xuecheng; Ouyang, Hanbin; Zhao, Dongliang; Huang, Gang; Deng, Yuping; Huang, Wenhua (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: To evaluate the biomechanical effects of Poller screws combined with small-diameter intramedullary nails in the treatment of distal tibial fractures at different locations and on different planes. Methods:Finite element modeling simulated the placement of intramedullary nails and poller screws for distal tibial fractures.Construct stiffness and directional micro-motion through the fracture were investigated to assess the poller effects of Poller screws. The allowable stress method was used to evaluate the safety of the construct. Results: Under the load condition of 500N, the mean axial stiffness with IMN only was 973.38±95.65 N/mm, which was significantly less than that in the two PS groups at positions A and B(P＜0.05).The shear displacements in the two PS groups at positions A and B were all smaller than the shear displacements of the models containing only intramedullary nail: 2.10mm±0.02mm (P<0.05). Under physiological load, the stresses of all internal fixation devices and the nail-bone interface were within a safe range. Conclusion: In the treatment of distal tibial fractures, placing the poller screw in the proximal fracture block can obtain better biomechanical performance.The intramedullary fixation system can obtain higher structural stiffness and reduce the displacement of the fracture end by adding poller screws.